A field study on the impacts of implementing concepts and elements of industry 4.0 in the biopharmaceutical sector - Silva, Felipe (2022)
This study proposes a field study, based on a literature review, about the applications and impacts of Industry 4.0 (I4.0) in the biopharmaceutical sector. The world is facing a new industrial revolution and the central idea is the integration between the virtual and the real world through elements that will allow for a greater degree of automation and digitization of processes. The production of medicines via biological processes is a booming domain in the pharmaceutical sector, that involves extraordinary technological challenges. The fieldwork, carried out between August 2019 and February 2020, involved semi-structured interviews with managers of pharmaceutical companies and specialists in the I4.0 theme. The interviews allowed for the identification of trends and key benefits and barriers for implementing I4.0 in the biopharmaceutical sector. While the perceptions were considerably diversified, benefits in productivity, competitiveness and quality ranked among the most scored items. The main barriers, highlighted by the interviewees, refer to the need to break organizational cultural standards, the regulatory requirements, the lack of organizational strategies for implementation, and the lack of qualified professionals. This work offers a contribution to the biopharmaceutical sector and reinforces the imminent need for companies to adapt to this new reality.